A library of templates of iterative Krylov subspace methods for the numerical solution of continuum mechanics problems on hybrid computing systems - Gubajdullin, D.A.; Nikiforov, A.I.; Sadovnikov, R.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2010)
A library of C++ templates of iterative Krylov subspace methods with preconditioning for the solution of large sparse systems of linear algebraic equations on modern NVIDIA graphics processors is considered. The methods can be used on single or multiple graphics processor units simultaneously, i.e., on the so-called hybrid computing systems on which the computations on central processor units are combined with the computations on graphics processor units. The library is intended for those who need to solve large sparse systems of linear algebraic equations.